Genetic diversity of Amorphophallus titanum in Bengkulu, Indonesia based on RAPD markers - WAHYUDI ARIANTO; ERVIZAL A.M. ZUHUD; AGUS HIKMAT; TUTUT SUNARMINTO; ISKANDAR Z. SIREGAR (Biodiversitas Journal of Biological Diversity, 2018)
Arianto W, Zuhud EAM, Hikmat A, Sunarminto T, Siregar IZ. 2018. Genetic diversity of Amorphophallus titanum in Bengkulu, Indonesia based on RAPD markers. Biodiversitas 19: 1783-1790. Titan Arum [Amorphophallus titanum (Becc.) Becc. Ex Arcang], a plant species belonging to the family of Araceae is known for its gigantic floral size and elicited rotten fragrance when the flower bloom. Since it remains only found in Sumatran island, many authors categorized the plant as endemic species. The population of the species in the natural habitat has significantly declined because of the conversion of forest land mainly into plantations or other land uses. Considering the importance of conservation attempts to A. titanum, a sufficient data on genetic diversity of the species is necessary. The research was aimed to determine the genetic diversity within and among populations of A. titanum in some area of protected forests in Bengkulu Province, comprising the population of Palak Siring, Tebat Monok, and Air Selimang. RAPD genetic DNA fingerprinting approach was used to assess the genetic diversity of A. titanum using 13 preselected DNA primer: OPA 11, OPA 19, OPC 04, OPN 14, OPN 19, OPU 03, OPU 06, OPU 07, OPB 17, OPC 07, OPO 04, OPU03-1, OPNI 18E. The result revealed that the method has successfully produced several DNA fragments with varied length ranging from 250 bp to 2000 bp with 4-16 variation in polymorphic bands. Based on RAPD marker analysis, the population of Air Selimang was considered as a potential center of diversity of A. titanum because of the others two populations had a lower genetic diversity. In general, the genetic diversity among populations was lower than within population. The cluster analysis of the genetic similarity of 22 individuals of the three populations resulted in the separation into two main groups with the first group consisting of 17 individuals (Population Air Selimang and Tebat Monok) and the second group of 5 individuals (Palak Siring population).